CFD Simulation of Heat Transfer and Turbulent Fluid Flow over a Double Forward-Facing Step. (16th December 2013) - Togun, Hussein; Shkarah, Ahmed Jassim; Kazi, S. N.; Badarudin, A.
Abstract : Heat transfer and turbulent water flow over a double forward-facing step were investigated numerically. The finite volume method was used to solve the corresponding continuity, momentum, and energy equations using the K - ε model. Three cases, corresponding to three different step heights, were investigated for Reynolds numbers ranging from 30, 000 to 100, 000 and temperatures ranging from 313 to 343 K. The bottom of the wall was heated, whereas the top was insulated. The results show that the Nusselt number increased with the Reynolds number and step height. The maximum Nusselt number was observed for case 3, with a Reynolds number of 100, 000 and temperature of 343 K, occurring at the second step. The behavior of the Nusselt number was similar for all cases at a given Reynolds number and temperature. A recirculation zone was observed before and after the first and second steps in the contour maps of the velocity field. In addition, the results indicate that the coefficient pressure increased with increasing Reynolds number and step height. ANSYS FLUENT 14 (CFD) software was employed to run the simulations.